2019
DOI: 10.1371/journal.pone.0218157
|View full text |Cite
|
Sign up to set email alerts
|

Individual, community and service environment factors associated with modern contraceptive use in five Sub-Saharan African countries: A multilevel, multinomial analysis using geographically linked data from PMA2020

Abstract: The importance of the family planning service environment and community-level factors on contraceptive use has long been studied. Few studies, however, have been able to link individual and health facility data from surveys that are nationally representative, concurrently fielded, and geographically linked. Data from Performance Monitoring and Accountability 2020 address these limitations. To assess the relative influences of the service delivery environment and community, household, and individual factors on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 35 publications
8
42
1
Order By: Relevance
“…These ndings are supported by previous evidence that traditional gender norms that support higher ideal number of children, early marriage, domestic violence or female unemployment reduced women's ability to meet their family planning needs [34][35][36]. Also, promoting women's education, autonomy, HIV knowledge, and contact with family planning health workers were shown to increase modern contraceptive use among women [34,35,37]. In patriarchal societies, violence and discrimination are used to maintain women in a socially disadvantaged position and legitimize their subordinate position [38].…”
Section: Gender Norms At the Community-levelsupporting
confidence: 63%
“…These ndings are supported by previous evidence that traditional gender norms that support higher ideal number of children, early marriage, domestic violence or female unemployment reduced women's ability to meet their family planning needs [34][35][36]. Also, promoting women's education, autonomy, HIV knowledge, and contact with family planning health workers were shown to increase modern contraceptive use among women [34,35,37]. In patriarchal societies, violence and discrimination are used to maintain women in a socially disadvantaged position and legitimize their subordinate position [38].…”
Section: Gender Norms At the Community-levelsupporting
confidence: 63%
“…Currently married women aged 15–24 years, those living with a partner or previously married and not living with a partner were more likely to terminate pregnancy than never-married women. This could be linked to social desirability bias as never-married 15–24 year old women may be reluctant to report pregnancy termination due to social stigma surrounding non-marital sexual activity or use of contraceptive [ 46 ]. However, this is inconsistent with the findings of previous school-based studies in Nigeria [ 16 , 18 ] and facility-based studies among older women in Ethiopia [ 23 ], Burkina Faso [ 47 ] and Ghana [ 22 ], which found that unmarried youth are more likely to terminate a pregnancy than their married counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…The review brought out three major categories of barriers that deter young people from SRH services patronage: barriers of service-accessibility that discourage or prevent them from accessing SRH services; barriers of service-utilization that young people experience from the time they entered the SRH services facility till they exit and that of service-quality which are encountered at the time of receiving service. [67,68].…”
Section: Discussionmentioning
confidence: 99%